How Reliable Is the Intraoperative Computed Tomography Angiography in Assessing Complete Surgical Resection of Cerebral Arteriovenous Malformations?. Issue 6 (25th August 2021) - Alotaibi, Fahad Saud; Ntyl, Sondous Raid; Almuhaini, Tafla Saleh; Bin Abdulqader, Sarah; Alotaibi, Naif M; Soulami, Lahbib; Bafaquh, Mohammad; Al Yamany, Mahmoud; Alturki, Abdulrahman Y; Alzhrani, Gmaan; Orz, Yasser; Alobaid, Abdullah
Abstract: BACKGROUND: Digital subtraction angiography (DSA) is still considered the gold standard test to evaluate arteriovenous malformation's (AVM) residual after microsurgical resection. OBJECTIVE: To evaluate the safety and reliability of intraoperative computed tomography angiography (iCTA) as an immediate method of evaluating the surgical results of AVM resection. METHODS: We performed a retrospective review for all cases of cerebral AVMs at our institute from January 2015 to April 2020 who underwent surgical resection of cerebral AVM and had iCTA. All included patients underwent a postoperative DSA, and the results were compared with iCTA. RESULTS: Twenty-eight cases were included. All cases showed complete resection (100%) in the iCTA, and the results were consistent with the postoperative DSA results. The sensitivity of iCTA was 100%. The added operative time ranged from 25 to 30 min. There were no complications related to the use of iCTA. CONCLUSION: Intraoperative assessment of AVMs surgical results with an iCTA is safe and reliable. The sensitivity of iCTA following AVM resection merits further investigations.